WELCOMING PRACTICE IN PSYCHOSOCIAL CARE FOR THE PERSON-CENTERED CARE - Sousa, Johnatan Martins; Farinha, Marciana Gonçalves; Landim, Joyce Soares Silva; Lucchese, Roselma; Paranaguá, Thatianny Tanferri de Brito; Nunes, Fernanda Costa; Bezerra, Ana Lúcia Queiroz (Cogitare Enfermagem, 2023)
Objective: To analyze the practice of welcoming people into psychosocial care for person-centered care. Method: A qualitative, strategic social research study based on the Person-Centered Clinical Method, conducted with 17 professionals from two Psychosocial Care Centers in the Central Region of Brazil. Data were collected using a questionnaire to characterize the profession and individual online interviews between June and August 2021. The data was subjected to thematic content analysis. Results: the thematic category "Practice of welcoming in psychosocial care" included three categories that showed what is practiced by professionals in welcoming: 1. Family issues; 2. Health issues; 3. Psychosocial issues. Final considerations: there has been progress in the welcoming practices of some professionals, which is closer to the psychosocial care model, but there is a need for ongoing education so that person-centered welcoming becomes a common action in the services.